Pharmacologic Modulation of Hand Pain in Osteoarthritis: A Double‐Blind Placebo‐Controlled Functional Magnetic Resonance Imaging Study Using Naproxen1. Issue 3 (March 2015) - Sanders, Duncan; Krause, Kristina; O'Muircheartaigh, Jonathan; Thacker, Michael A.; Huggins, John P.; Vennart, William; Massat, Nathalie J.; Choy, Ernest; Williams, Steven C. R.; Howard, Matthew A.
<x xml:space="preserve">Abstract</x> Objective In an attempt to shed light on management of chronic pain conditions, there has long been a desire to complement behavioral measures of pain perception with measures of underlying brain mechanisms. Using functional magnetic resonance imaging (fMRI), we undertook this study to investigate changes in brain activity following the administration of naproxen or placebo in patients with pain related to osteoarthritis (OA) of the carpometacarpal (CMC) joint. Methods A placebo‐controlled, double‐blind, 2‐period crossover study was performed in 19 individuals with painful OA of the CMC joint of the right hand. Following placebo or naproxen treatment periods, a functionally relevant task was performed, and behavioral measures of the pain experience were collected in identical fMRI examinations. Voxelwise and a priori region of interest analyses were performed to detect between‐period differences in brain activity. Results Significant reductions in brain activity following treatment with naproxen, compared to placebo, were observed in brain regions commonly associated with pain perception, including the bilateral primary somatosensory cortex, thalamus, and amygdala. Significant relationships between changes in perceived pain intensity and changes in brain activity were also observed in brain regions previously associated with pain intensity. Conclusion This study demonstrates the sensitivity of fMRI to detect the mechanisms underlying treatments of known efficacy. The data illustrate the enticing potential of fMRI as an adjunct to self‐report for detecting early signals of efficacy of novel therapies, both pharmacologic and nonpharmacologic, in small numbers of individuals with persistent pain.